The Study of Different Factors’ Effects on the Oil Futures Price by Applying Agent-based Model - Karimi, Mohammad sadegh; Maleki, Abbas (International Journal of Energy Economics and Policy, 2018)
An agent-based model is employed for simulating the price of oil futures. The model proceeds as follows: On each time step agents choose their rule for price expectation formation. Next, they bid and ask based on their price and trend expectations. The new price is formed using “the market mechanism”. Finally, the time steps forward and the process is repeated in the next day. The agents use 6 different rules to make price and trend expectations. Brent future prices in a 2-year-period (2010 to 2011) and in 2012 are used for model calibration and validation, respectively. It was shown that market participants weigh U.S. stocks data more than other factors, while OECD stock’s data were not that important for the market. It was also inferred that the market does not weigh the technical aspects of the oil price as much as the fundamental aspects. Keywords: Agent-based model, oil price, technical/fundamental rule JEL Classifications: C4, C5, Q3, Q4